A comparative method for protein extraction and 2-D gel electrophoresis from different tissues of Cajanus cajan - Singh, Nisha; Jain, Neha; Kumar, Ram; Jain, Ajay; Singh, Nagendra K.; Rai, Vandna (Frontiers in Plant Science, 2015)
Pigeonpea is an important legume crop with high protein content. However, it is often subjected to various abiotic and biotic stresses. Proteomics is a state-of-the-art technique used to analyze the protein profiling of a tissue for deciphering the molecular entities that could be manipulated for developing crops resistant to these stresses. In this context, developing a comprehensive proteome profile from different vegetative and reproductive tissues has become mandatory. Although several protein extraction protocols from different tissues of diverse plant species have been reported, there is no report for pigeonpea. Here, we report tissue-specific protein extraction protocols representing vegetative (young leaves), and reproductive (flowers and seeds) organs and their subsequent analysis on 2-dimensional gel electrophoresis. The study explicitly demonstrated that the efficacy of a particular protein extraction protocol is dependent on the different tissues, such as leaves, flowers and seeds that differ in their structure and metabolic constituents. For instance, phenol-based protocol showed an efficacy towards higher protein yield, better spot resolution and a minimal streaking on 2-DE gel for both leaves and flowers. Protein extraction from seeds was best achieved by employing phosphate-TCA-acetone protocol.